User-Level Transaction Scheduling in Haskell - Duarte, Rodrigo Medeiros; Du Bois, André Rauber; Cavalheiro, Gerson Geraldo Homrich; Pilla, Maurício Lima (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2018)
Transactional Memory is an abstraction that helps concurrent programming, however, in high contention sceneries, it presents low performance because of the high conﬂict rate between transactions. In this work, we present four transactional schedulers implemented entirely in Haskell using different abstraction levels. The results present, despite the inherent overhead of highlevel implementations, a reduction in the conﬂict rates.